Implementasi Model Pembelajaran Kooperatif Tipe STAD pada Pembelajaran Pancasila Meningkatkan Hasil Belajar Siswa Kelas VIII A SMP Muhammadiyah Singaraja - Haqi Nabila Cahyanti; I Made Yudana; Ni Nyoman Asri Sidaryanti; I Wayan Kertih; I Putu Windu Mertha Sujana (Simpati, 2026)
This study aims to improve students’ learning outcomes through the implementation of the cooperative learning model of Student Teams Achievement Division (STAD) in the Pancasila Education subject for class VIII A at SMP Muhammadiyah Singaraja. This research employed a Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 29 students of class VIII A. Data were collected using learning achievement tests and observation sheets. The collected data were analyzed using descriptive quantitative techniques to evaluate students’ academic progress during each cycle. The findings indicate that the implementation of the STAD learning model contributed positively to improving students’ learning outcomes, participation, and engagement in classroom activities. Therefore, the STAD cooperative learning model can be considered an effective instructional strategy for enhancing learning achievement in Pancasila Education.